"English Day" sebagai Upaya Meningkatkan English Exposure bagi Siswa-Siswi SMPN 2 Ulujami, Pemalang - Jumaroh, J (Prosiding University Research Colloquium, 2020)
Exposure is an important feature in English learning. However, lack of exposure is a major problem we have since English is only a foreign language in Indonesia. Therefore, a program called ‘English Day’ was conducted to provide additional exposure of English for the participants, who were 30 junior high school students. The program was carried out in two days. All activities, approach, and learning material being implemented here were chosen based on the need analysis conducted before the main program. To assess the effectiveness of the program, the participants were aksed to fill in a questionnaire at the beginning and by the end of ‘English Day’. The result of the questionnaire showed that this program could raise students’ enthusiasm (60% became 97%), motivation (70% became 100%), and courage to speak English (3% became 80%). Therefore, ‘English Day’ is strongly recommended to be conducted by teachers of English to familiarize their students to English.